Puerto Rico Bridge to Freedom - McGuire, Edna (London The Macmillan Company, 1963)
From the bold adventures of Cristopher Columbus and the Spanish conquistadors to the sweeping programs of twentieth-century progress, this book tells the fascinating story of Puerto Rico.
Keywords: Politics